Clinical Outcomes of Accelerated Corneal Cross-Linking for Pediatric Keratoconus - Abdelrahman Salman; Taym Darwish; Marwan Ghabra; Obeda Kailani; Hussam Khalil; Rafea Shaaban (Journal of Ophthalmology)
Aim. To assess the efficacy and safety of accelerated corneal cross-linking in the treatment of pediatric keratoconus. Method. In this retrospective case series, 29 eyes of 20 pediatric patients with keratoconus underwent accelerated corneal cross-linking. Treatment was delivered at 10 mW/cm2 for 9 minutes with a total dose of 5.4 J/cm2. Clinical evaluation included visual acuities and refractive and Scheimpflug corneal tomography assessments. All patients with a minimum follow-up duration of 24 months were included in the study. Results. Mean ± standard deviation age was 15.41 ± 2.13 years (range: 8 to 18 years). Uncorrected distance visual acuity improved significantly from 0.56 ± 0.28 to 0.42 ± 0.29 logMAR P=0.0003, and corrected distance visual acuity improved significantly from 0.34 ± 0.23 to 0.28 ± 0.22 logMAR P=0.014. The mean manifest refraction spherical equivalent value was significantly reduced (−0.59 ± 0.95 D, P=0.0024). While mean flat keratometry and steep keratometry values were not significantly altered (P>0.05 for both), the mean maximum keratometry value was significantly decreased from 56.97 ± 5.24 D preoperatively to 55.84 ± 5.37 D at 24 months postoperatively P=0.003. Maximum keratometry had progressed by >1 D in two eyes (6.89%). Permanent corneal haze was reported in one case (3.44%). Conclusion. Our 24-month follow-up demonstrated that accelerated corneal cross-linking appears to halt the progression of keratoconus in pediatric patients without apparent complications. Uncorrected and corrected distance visual acuities were also improved.